2015
DOI: 10.1007/s11356-015-4681-6
|View full text |Cite
|
Sign up to set email alerts
|

Insecticides induced biochemical changes in freshwater microalga Chlamydomonas mexicana

Abstract: The effect of insecticides (acephate and imidacloprid) on a freshwater microalga Chlamydomonas mexicana was investigated with respect to photosynthetic pigments, carbohydrate and protein contents, fatty acids composition and induction of stress indicators including proline, superoxide dismutase (SOD) and catalase (CAT). C. mexicana was cultivated with 1, 5, 10, 15, 20 and 25 mg L(-1) of acephate and imidacloprid. The microalga growth increased with increasing concentrations of both insecticides up to 15 mg L(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 47 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Toxicity of IMI on aquatic photosynthetic organisms has been scarcely studied. Specifically, the available information is limited to growth inhibition of the macrophyte Lemna gibba (EC 50 = 740 mg/L; Daam et al., 2013) and unicellular algae (LC 50 = 20 mg/L for Chlamydomonas mexicana and NOEC = 10 mg/L IMI for Scenedesmus subspicatus ; Kumar et al., 2015; IUPAC PPDB, 2018). Particularly, genotoxicity in photosynthetic organisms has been reported in terrestrial model species.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity of IMI on aquatic photosynthetic organisms has been scarcely studied. Specifically, the available information is limited to growth inhibition of the macrophyte Lemna gibba (EC 50 = 740 mg/L; Daam et al., 2013) and unicellular algae (LC 50 = 20 mg/L for Chlamydomonas mexicana and NOEC = 10 mg/L IMI for Scenedesmus subspicatus ; Kumar et al., 2015; IUPAC PPDB, 2018). Particularly, genotoxicity in photosynthetic organisms has been reported in terrestrial model species.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects of bioaccumulations to the microalgal cells are countered by the production of antioxidative enzymes that can eliminate excessive ROS by scavenging these free radicals [115]. It was reported that insecticides acephate and imidacloprid with concentration of 15 mg/L induced an adaptive biochemical change in freshwater microalgae Chlamydomonas mexicana, where superoxide dismutase activity (SOD) antioxidant enzyme was significantly increased as part of the defense mechanisms [116]. The photosynthetic algae native to polar regions, Cocomyxa subellipsoidea hydrolyze and breakdown paraoxon, malathion and diazinon organophosphates through the formation of ROS have been demonstrated [117].…”
Section: Bioremediation Of Pesticides Using Microalgae: Why and Howmentioning
confidence: 99%
“…• -superoxide radicals, OH • -hydroxyl radical, HO 2 • -perhydroxy radical, and RO • -alkoxy radicals) and nonradical forms (e.g., H 2 O 2 -hydrogen peroxide and 1 O 2 -singlet oxygen). At normal levels, these species act as essential signaling molecules to control cellular metabolism; however, at excess levels, these species can cause severe damage to cellular components and an increased rate of mutagenesis that ultimately leads to programmed cell death [167]. Such as for fungi, pollutant degradation by algae seems to involve intracellular and extracellular enzymatic systems (Figure 3).…”
Section: Mechanisms Of Removalmentioning
confidence: 99%